Web-Based Integration of IoT and Artificial Intelligence for Monitoring Aquariums - Nugraha, Ananto Indra; Rosita, Yesy Diah (MATICS: Jurnal Ilmu Komputer dan Teknologi Informasi (Journal of Computer Science and Information Technology), 2024)
Technology is now an indispensable part of work across all fields and locations. For instance, in fish cultivation and among ornamental fish enthusiasts, technology plays a pivotal role in regulating and notifying when ornamental fish's environmental conditions require attention. This includes monitoring and alerting for cleaning or feeding needs. Ornamental fish are particularly sensitive, often carrying a higher price tag. Due to their susceptibility to stress and their relatively costly nature, those involved in ornamental fish cultivation and collection frequently face significant losses. These losses can occur when fish are collected, raised, and fall ill or, in the worst-case scenario, die. In response to these challenges, technological innovations have emerged to simplify the monitoring of ornamental fish's environmental conditions. This is achieved through IoT-based solutions accessible anytime and anywhere via the web. These innovations incorporate three primary sensors: pH sensors, clarity sensors, and temperature sensors. Additionally, Thingsboard is used to facilitate real-time monitoring of sensor data. These aquarium monitoring systems for ornamental fish hold the potential to enhance fish welfare and health, mitigate risks, and provide hobbyists and professionals with a more effective and informed experience in maintaining ornamental fish. However, it's important to note that the success of this system relies heavily on the quality of hardware, meticulous software development, and a profound understanding of the specific needs of ornamental fish